Unequal Impact of COVID-19 on Private and Academic Neurosurgical Workforce: Results of an International Survey - Ridwan, Sami; Ganau, Mario; Zoia, Cesare; Broekman, Marike; Grote, Alexander; Clusmann, Hans (Frontiers in Surgery, 2021)
Background: Since the COVID-19 outbreak several manuscripts regarding neurosurgical practice during this pandemic have been published. Qualitative studies on how the pandemic affected neurosurgeons, with additional focus on their practice, are still scarce. This study’s objective was to investigate the impact of COVID-19 on various aspects of the professional and private life of a homogeneous group of international neurosurgeons affiliated to the European Association of Neurosurgical Societies (EANS). Methods: Neurosurgeons from Europe and abroad were invited to participate in an online survey endorsed by the Individual Membership Committee of the EANS. The survey captured a subjective snapshot of the impact of the first wave of the COVID-19 pandemic on EANS members and was advertised through its Institutional website. In addition to departmental data, personal feeling of safety, financial security, local precautions, number of surgeries performed, changes in daily routine, and other practice-related information were inquired. Differences among practice types were closely reviewed. Results: The survey was distributed between April and May 2020: 204 neurosurgeons participated. Participants were typically active EANS members (73%), consultants (57.9%), from university hospitals (64.5%). Elective surgical practice was still ongoing only for 15% of responders, whereas 18.7% of them had already transitioned to COVID-19 and emergency medical services. While 65.7% of participants thought their institutions were adequately prepared, lack of testing for SARS-CoV-2, and scarcity of personal protective equipment were still a matter of concern for most of them. Overall surgical activity dropped by 68% (cranial by 54%, spine by 71%), and even emergencies decreased by 35%. COVID-19 prompted changes in communication in 74% of departments, 44% increased telemedicine by >50%. While most neurosurgeons had concerns about personal and families’ health, financial outlook appeared to be gloomy only for private practitioners. Conclusion: The lockdown imposed in many countries by the COVID-19 outbreak called for immediate modification of working routine and resulted in a dramatic decrease of elective surgical procedures. Neurosurgeons share common concerns but were not equally exposed to the personal health and financial dangers of the ongoing pandemic.